Entrevista com lideranças na promoção da ética em pesquisa e da integridade acadêmica e científica - Coutinho, Angela Scalabrin; Leite, Sandra Fernandes; Foltýnek, Tomáš; Forgas, Rubén Comas; Fernandes, Frederico Garcia; Vasconcelos, Sonia Maria Ramos; Mainardes, Jefferson (Práxis Educativa, 2023)
Entrevistadoras: Angela Scalabrin Coutinho Sandra Fernandes Leite Entrevistados: Tomáš Foltýnek Rubén Comas Forgas Frederico Garcia Fernandes Sonia Maria Ramos Vasconcelos Jefferson Mainardes